Biotechnological efficiency of auxins from lentils (Lens culinaris) as rooting in cocoa seedlings - Montaño-Luis, Cagua; Gómez-Betty, Pazmiño; Guamán-Alonso, Andaluz; Granados-Carlos, Aguilar; Avila-Job, Andrade; Logo-Jaleny, Mejía (REDIELUZ, 2024)
In Ecuador, the production of Theobroma cacao L. is primarily concentrated in the provinces of Los Ríos, Guayas, Manabí, and Sucumbíos. Its propagation is carried out either sexually through seeds or asexually using cuttings, layering, or grafting, particularly to ensure optimal development and growth of the plant. As a biotechnological alternative, the use of a natural phytohormone (auxin) derived from lentil extract has been explored to support root development and growth in cacao seedlings. Studies conducted on different treatments, including T1 (control), T2 (lentil extract), and T3 (urea), demonstrated that the best results were obtained with the lentil extract (T2). This treatment resulted in an average root length of 47 cm, six roots per seedling, and leaf length of 23 cm in cacao seedlings. Lentil extract, which contains auxin phytohormones, proved effective when applied during the growth and development stages of cacao seedlings. Its application significantly enhanced foliage growth, root system development, and increased the number of roots.